Fundamentals of Construction Estimating - Pratt, David J, 1946- (Boston : Cengage, 2019)
"This comprehensive resource offers thorough instruction on the principles of construction estimating and helps readers develop the skills they need to become professional estimators. FUNDAMENTALS OF CONSTRUCTION ESTIMATING, Fourth Edition, presents estimating procedures in a straightforward and engaging way, clearly explaining key processes of estimating and costing construction work such as quantity takeoff; pricing of contractor work, sub-trade work, and site overhead; and compiling bid documents. In addition, the text includes drawings of two major projects--one residential and one commercial--to guide readers through a complete estimating process that can be followed by various trades on many different types of construction projects"--Publisher's website.
1 Introduction. -- 2 The BID Process and Preliminary Procedures -- 3 Measuring Quantities Generally -- 4 Measuring Sitework, Excavation and Piling -- 5 Measuring Concrete Work -- 6 Measuring Masonry Work. -- 7 Measuring Carpentry and Miscellaneous Items -- 8 Pricing Generally. -- 9 Pricing Construction Equipment. -- 10 Pricing Excavation and Backfill. -- 11 Pricing Concrete Work -- 12 Pricing Masonry, Carpentry and Finishes Work -- 13 Pricing Subcontractors' Work -- 14 Pricing General Expenses. -- 15 Closing the Bid -- 16 Budget Estimating -- 17 Elemental Estimating -- 18 Life-Cycle Costing. -- Appendix Glossary -- Index.
Includes glossary and index.
Previous edition 2011.
Keywords: Building -- Estimates; Building -- Estimates; TECHNOLOGY & ENGINEERING / Construction / Estimating; Building -- Estimates; Building -- Estimates -- Data processing